Economic Valuation of “Parak” Traditional Agroforestry West Sumatera (Case Study in Nagari Paninggahan, Solok Regency) - Helmayuni; Mardianto (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2021)
This study aims to determine the economic value, which is a direct and indirect benefit (tangible and intangible) of Parak in the research area. This research used a case study method, and the sampling was carried out in a purposive manner consisting of 50 sample farmers. The data used in this study are primary data and secondary data. Preliminary data were obtained by direct interviews with respondents based on the questionnaire provided, while secondary data were taken from agencies related to this research. The processing of data obtained in the field shows that Parak plays an important role in supporting the economy of farmers in Nagari Paninggahan either directly or indirectly. The direct use value obtained from the plant is IDR. 46,753,650 (66,316 per cent), from firewood of IDR. 23,070,000 (32,722 percent) and from livestock IDR. 678,550 (0.963 per cent) so that the total direct use income is IDR. 70,502,200 per year of all commodities cultivated by the sample farmers. Meanwhile, for indirect use, such as household/domestic water use, IDR. 13,312,320/year and agricultural irrigation water IDR. 54,052,111/year. The total indirect usage is IDR. 67,364,431,-. Per year. Agroforestry patterns can cover the soil layer well and have an effective influence on soil erosion control to increase the supply of water in the soil. Respondents have also carried out other conservation activities by constructing bench terraces, terracing systems, and other buildings to suppress sedimentation and erosion.